2013
DOI: 10.1038/ncomms2491
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix inhibits structural and functional plasticity of dendritic spines in the adult visual cortex

Abstract: Brain cells are immersed in a complex structure forming the extracellular matrix. The composition of the matrix gradually matures during postnatal development, as the brain circuitry reaches its adult form. The fully developed extracellular environment stabilizes neuronal connectivity and decreases cortical plasticity as highlighted by the demonstration that treatments degrading the matrix are able to restore synaptic plasticity in the adult brain. The mechanisms through which the matrix inhibits cortical plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
108
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 39 publications
5
108
0
Order By: Relevance
“…Growing evidence supports the view that dynamic ECM changes may be involved in providing important cues for synaptic stabilization or reorganization in the adult brain (2,16). For instance, lack of components of the ECM in adult mice correlates with altered synaptic activity and plasticity (12,14,35). In our study, we have demonstrated that enzymatic ECM removal in ACx of adult Mongolian gerbils did not influence cortex-dependent learning of a new task or memory retrieval of an already established discrimination strategy.…”
Section: Potential Cellular Mechanisms Of Ecm-derived Modulation Ofsupporting
confidence: 61%
See 3 more Smart Citations
“…Growing evidence supports the view that dynamic ECM changes may be involved in providing important cues for synaptic stabilization or reorganization in the adult brain (2,16). For instance, lack of components of the ECM in adult mice correlates with altered synaptic activity and plasticity (12,14,35). In our study, we have demonstrated that enzymatic ECM removal in ACx of adult Mongolian gerbils did not influence cortex-dependent learning of a new task or memory retrieval of an already established discrimination strategy.…”
Section: Potential Cellular Mechanisms Of Ecm-derived Modulation Ofsupporting
confidence: 61%
“…On a more general account, our data show that the ECM might serve an important function for the regulation of stability and plasticity in learning-relevant synaptic networks. Recent findings implicate that structural changes in cortical circuits at the level of dendritic spines and individual synaptic rearrangements provide long-term information storage of prior experiences (12). On this microscopic level, the release or activation of ECM-removing or -modifying enzymes can indeed promote necessary neuronal adaptations to regulate learning-related plastic changes.…”
Section: Potential Cellular Mechanisms Of Ecm-derived Modulation Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…injection of urethane (1-1.5 g/kg). Craniotomy (2-to 3-mm diameter) was performed as described elsewhere, and the dura mater was removed to reduce light scattering (58). A custom-made steel head post with a central imaging chamber was glued to the skull.…”
Section: Methodsmentioning
confidence: 99%